National and Organizational Culture, Performance Evaluation and Trust: Evidence from Multinational Company Subsidiary in Indonesia - Unggul Purwohedi (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
The aim of this study is to investigate the impact of national and organizational culture on the relationship between accounting and trust in a subsidiary of a Western Multi-National Company (MNC) in Indonesia. This study use a qualitative field study of one French MNC subsidiary and interview four expatriate directors, nine Indonesian managers and 10 Indonesian employees. Key themes were identified with the assistance of NVivo software. In this study, accounting, through formal performance evaluation, contributes to trust building between supervisors and their subordinates. Formal performance evaluation through transparent and objective evaluation increases trust in the supervisor. On the other hand, informal performance evaluation tends to decrease trustful behaviour due to secrecy in the evaluation process. It appears that Indonesian national culture does influence organizational culture preference in the local staff. Individuals share national culture as a result of values developed from family, religion, education, and experience.DOI: 10.15408/sjie.v6i2.4733